The Influence of Green Trust and Green Brand Image on Islamic Bank Customer Loyalty The Moderating Role of Eco-Labeling Awareness - Aulya Risky Afradini; Yenik Lidiawati; Sumin; Luqman; Nur Atiqah (Penerbit Jurnal Indonesia, 2026)
The banking sector is undergoing a transformation toward sustainable business models to mitigate climate change risks, yet the emergence of